PHARMACOECONOMIC STUDY OF OLMESARTAN/LERCANIDIPINE AND OFENOPRIL/LERCANIDIPINE COMBINATIONS IN THE TREATMENT OF PATIENTS WITH ESSENTIAL HYPERTENSION - D. S. Kaskaeva; M. M. Petrova; O. V. Zimnitskaya (Фармакоэкономика, 2017)
Objective. Pharmacoeconomic analysis of the use of combinations of antihypertensive drugs were olmesartan/lercanidipine and zofenopril/lercanidipine in patients with essential hypertension II-III stage.Materials and methods. The authors performed prospective randomized uncontrolled study. Were examined in 27 people essential hypertension with II-III stage age from 40 to 71 years before and after the use of combinations of drugs olmesartan/lercanidipine and zofenopril/lercanidipine. An ABC/VEN-analysis, сost-effectiveness analysis, comparative assessment of the incidence of side effects of the studied drugs were performed.Results. Anti-hypertensive effect of the studied combinations of drugs were not significantly different and equally effectively reduced blood pressure. But the cost of blood pressure reduction at 1 mm Hg was the smallest in the group zofenopril/lercanidipine.Conclusion. The results of pharmacoeconomic analysis to be more cost-effective combination for the treatment of patients with essential hypertension II-III stage is the combination of zofenopril/lercanidipine.